Pengaruh Opportunities, Kepemilikan Manajerial, Investment Opportunity Set, Risiko Litigasi, dan Intensitas Modal Terhadap Konservatisme Akuntansi - Nida Hanifah; Kusumawati, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Accounting conservatism is a concept and prudential principle that recognizes costs and losses early, slows down revenue and profit recognition, lowers asset valuations and raises liability assessments. This study aims to analyze the effect of opportunities, managerial ownership, investment opportunity set, litigation risk, and capital intensity on accounting conservatism in non-financial companies on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used in this study was purposive sampling. A total of 438 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results provide empirical evidence that opportunities and litigation risk affect accounting conservatism. Meanwhile managerial ownership, investment opportunity set, and capital intensity have no effect on accounting conservatism.